Rasionalitas Beragama Pekerja Seks Komersial (PSK) - Rahmi Putri; Syafruddin Syafruddin (Indonesian Journal of Religion and Society, 2020)
This paper aims to explore religious rationality among prostitutes. This study is a case study with a qualitative descriptive method at the Panti Sosial Karya Wanita Andam Dewi Solok. Data was collected using in-depth interview techniques. Using Max Weber's rationality theory as an analytical tool, this study found several important findings. First, the choice to enter the world of prostitution is a rational action taken by prostitutes. The act of prostitution that is carried out is an action that is goal-oriented (instrumentally rational). Actions of prostitution are rationally strived to gain utility, either to show "himself" as a woman or as a person who is responsible in his family. Second, for prostitutes, between prostitution and religion, both are profitable. Prostitution can empower families and improve the economic sector, while religion can reduce and eliminate the sin of prostitution. Religion is not only interpreted as a doctrine that only regulates ritual aspects such as prayer, fasting and all kinds of things, but more than that religion is interpreted as an antidote for any sexual act committed in prostitution.